A robust watermarking framework for High Efficiency Video Coding (HEVC) - Encoded video with blind extraction process - Dutta T.; Gupta H.P. (My University, 2025)
Digital watermarking is an efficient and promising means for copyright protection of multimedia objects. Digital videos are stored and transmitted in a compressed format, which has drawn a great deal of attention in compressed domain watermarking for video. The embedding and extraction of watermark bits in compressed domain, therefore does not require complete decoding and re-encoding of the compressed video. There have been several compression standards for video. High Efficiency Video Coding (HEVC), a successor to H.264 Advanced Video Coding (AVC), is the latest standard for video compression with high compression efficiency. In this paper, we propose a robust watermarking framework with a blind extraction process for HEVC encoded video. A readable watermark is embedded invisibly in 4×4 intra predicted blocks of the HEVC encoded video. Our watermarking framework enforces security by exploring the spatio-temporal characteristics of the compressed video and a random key for selection of embedding regions. We also analyze the strengths of different compressed domain features of HEVC encoded video for implementing the embedding algorithm. Experimental results demonstrate that the proposed work restrict the increase in video bit rate and degradation of perceptual quality. The proposed framework can also survive filtering, compressions, and noise additions maintaining good quality and robustness. © 2016 Elsevier Inc. All rights reserved.